Increasing Consumers' Purchase Intentions Toward Fair-Trade Products Through Partitioned Pricing - David Bürgin; Robert Wilken (Journal of Business Ethics, 2021)
Selling fair-trade products can be problematic because of their higher price when compared with conventional alternatives. We propose that one way to solve this problem is to make consumers aware of the benefits of fair-trade. To this end, we perform three experimental studies to show that partitioned pricing (PP), which explicitly displays fair-trade as a separate price component, increases consumers' purchase intention toward the fair-trade product. This effect can be explained by increased perceptions of price fairness, which itself is mediated through transparency (but only if an additional verbal justification of the fair-trade price component is present). In the absence of such a verbal justification, recalled prices instead of transparency explain the positive effect of PP on consumers' purchase intentions. Interestingly, boundary conditions of this effect barely exist. Our incentive-aligned study illustrates that PP is associated with a 20% increase in purchases of fair-trade products. The results demonstrate an opportunity to increase the market share of fair-trade products, which increases social welfare and sustainability.
Keywords: 300; Fair-trade products; Partitioned pricing; Fairness; Purchase intention; Attitude–behavior gap; Price premium